THE EFFECT OF PROFITABILITY,CAPITAL INTENSITY,COMPANY SIZE AND INSTITUTIONAL OWNERSHIP ON TAX PLANNING (Empirical Study on CompaniesPropertiesAndReal Estatelisted on the Indonesia Stock Exchange (IDX) in 2018-2020) - Indriyani (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This study aims to examine the effect of profitability, capital intensity, firm size and institutional ownership on tax planning. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses secondary data with a population of all property and real estate companies listed on the Indonesia Stock Exchange in 2018-2020 with a total of 65 companies. Sampling decisions in this study used a purposive sampling method in which samples were selected based on certain criteria and obtained a sample of 66 financial reports from 22 property and real estate companies listed on the Indonesia Stock Exchange in 2018-2020. The statistical method used in this research is multiple linear regression analysis. The analytical methods used include descriptive statistical tests, classic assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. In addition, a test of the coefficient of determination and a hypothesis test were also carried out. The results showed that profitability and institutional ownership have a negative effect on tax planning. Meanwhile, capital intensity and company size have no effect on tax planning.